ENHANCEMENT OF THE AUCMEDI FRAMEWORK FOR MEDICAL IMAGE CLASSIFICATION - Gilang Pramudya, Aloysius
This thesis discusses the enhancement of the AUCMEDI framework for classifying medical problems from medical images. The primary challenge addressed is the limitation in the variety of image pre-processing methods, data augmentation techniques, and evaluation metrics available in the AUCMEDI framework. To